2015
DOI: 10.1007/s12035-015-9210-6
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Enrichment Improves Behavior, Cognition, and Brain Functional Markers in Young Senescence-Accelerated Prone Mice (SAMP8)

Abstract: The environment in which organisms live can greatly influence their development. Consequently, environmental enrichment (EE) is progressively recognized as an important component in the improvement of brain function and development. It has been demonstrated that rodents raised under EE conditions exhibit favorable neuroanatomical effects that improve their learning, spatial memory, and behavioral performance. Here, by using senescence-accelerated prone mice (SAMP8) and these as a model of adverse genetic condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 53 publications
3
59
0
1
Order By: Relevance
“…Our result also showed that EE could improve the learning and memory performance of VD model rats. A previous study concluded that EE applied to rodents results in regulatory mechanisms that give rise to significant beneficial effects at the molecular, cellular, and behavioral levels during brain development, particularly in the hippocampus [16]. BCCAO induces white matter and hippocampal damage, including microglial activation and proinflammatory mediator expression, and downregulation of the hyperphosphorylation of p38 MAPK signaling [17], and p38 MAPK signaling were also involved in other organs ischemia [18][19][20].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our result also showed that EE could improve the learning and memory performance of VD model rats. A previous study concluded that EE applied to rodents results in regulatory mechanisms that give rise to significant beneficial effects at the molecular, cellular, and behavioral levels during brain development, particularly in the hippocampus [16]. BCCAO induces white matter and hippocampal damage, including microglial activation and proinflammatory mediator expression, and downregulation of the hyperphosphorylation of p38 MAPK signaling [17], and p38 MAPK signaling were also involved in other organs ischemia [18][19][20].…”
Section: Discussionmentioning
confidence: 96%
“…The data are presented as the mean ± SD, and all computations were performed using SPSS [version 16.0]. One-way ANOVA and repeated-measures ANOVA were used.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The aim of the current study was to determine NF-κB signaling and Nrf2/ARE pathway related to inflammation and oxidation on the premature neurologic dysfunction in senescence accelerated mice. SAMP8 mouse model exhibits cognitive and emotional disturbances at a young age, probably due to pathological mechanisms such as inflammatory and oxidative signaling pathways [24]. Furthermore, this murine strain, SAMP8, has been described as a nature, non-transgenic tool for accelerated brain senescence [25].…”
Section: Discussionmentioning
confidence: 99%
“…The BDNF plays an intrinsic role in improving the synaptic plasticity and cognition by environmental enrichment (75,76).…”
Section: Ort and Oltmentioning
confidence: 99%